Fresno County Women Lawyers/Fresno County Bar Association Seminar on Judicial Selection Held at Ramada Inn - Watkins, Howard::::::::: (1989)
Justice Marvin Baxter, a former Judicial Appointments Secretary to Governor George Deukmejian, giving overview of the judicial selection process